Fleksibilitas Strategi dalam Era Globalisasi - Lengsi Manurung; Hugo Aries Suprapto (Peneliti.net, 2018)
This study aims to describe flexibility in the era of globalization. The method uses the literature review method. All documents, articles, books, scientific sources are processed and analyzed, and conclusions are given. The results of mass production research of standard products are no longer a feasible way to adopt the challenges of changing market demands, short product life cycles. In reality, the priority of competition based on cost, quality, time, flexibility or innovation and then paying attention to all resources to get something does not support competitive advantage. World-class factory owners must use strategic flexibility to overcome many uncertainties.